Increased ceruloplasmin expression caused by infiltrated leukocytes, activated microglia, and astrocytes in injured female rat spinal cords. Issue 7 (29th January 2018) - Wu, Yan; Shen, Lin; Wang, Rui; Tang, Jie; Ding, Shu‐Qin; Wang, Sai‐Nan; Guo, Xue‐Yan; Hu, Jian‐Guo; Lü, He‐Zuo
Abstract: Ceruloplasmin (Cp), an enzyme containing six copper atoms, has important roles in iron homeostasis and antioxidant defense. After spinal cord injury (SCI), the cellular components in the local microenvironment are very complex and include functional changes of resident cells and the infiltration of leukocytes. It has been confirmed that Cp is elevated primarily in astrocytes and to a lesser extent in macrophages following SCI in mice. However, its expression in other cell types is still not very clear. In this manuscript, we provide a sensible extension of these findings by examining this system within a female Sprague–Dawley rat model and expanding the scope of inquiry to include additional cell types. Quantitative reverse transcription polymerase chain reaction and Western blot analysis revealed that the Cp mRNA and protein in SCI tissue homogenates were quite consistent with prior publications. However, we observed that Cp was expressed not only in GFAP + astrocytes (consistent with prior reports) but also in CD11b + microglia, CNPase + oligodendrocytes, NeuN + neurons, CD45 + leukocytes, and CD68 + activated microglia/macrophages. Quantitative analysis proved that infiltrated leukocytes, activated microglia/macrophages, and astrocytes should be the major sources of increased Cp. Abstract : In this manuscript, we observed that ceruloplasmin (Cp) was expressed not only in astrocytes but also in microglia, oligodendrocytes, neurons, leukocytes, and activated microglia/macrophages after spinal cord injury. Quantitative analysis proved that infiltrated leukocytes, activated microglia/macrophages, and astrocytes are the major sources of increased Cp.